Caffeine in the management of patients with headache - Lipton, Richard B. (J Headache Pain, 2017)
Caffeinated headache medications, either alone or in combination with other treatments, are widely used by patients with headache. Clinicians should be familiar with their use as well as the chemistry, pharmacology, dietary and medical sources, clinical benefits, and potential safety issues of caffeine. In this review, we consider the role of caffeine in the over-the-counter treatment of headache. The MEDLINE and Cochrane databases were searched by combining “caffeine” with the terms “headache,” “migraine,” and “tension-type.” Studies that were not placebo-controlled or that involved medications available only with a prescription, as well as those not assessing patients with migraine and/or tension-type headache (TTH), were excluded. Compared with analgesic medication alone, combinations of caffeine with analgesic medications, including acetaminophen, acetylsalicylic acid, and ibuprofen, showed significantly improved efficacy in the treatment of patients with TTH or migraine, with favorable tolerability in the vast majority of patients. The most common adverse events were nervousness (6.5%), nausea (4.3%), abdominal pain/discomfort (4.1%), and dizziness (3.2%). This review provides evidence for the role of caffeine as an analgesic adjuvant in the acute treatment of primary headache with over-the-counter drugs, caffeine doses of 130 mg enhance the efficacy of analgesics in TTH and doses of ≥100 mg enhance benefits in migraine. Additional studies are needed to assess the relationship between caffeine dosing and clinical benefits in patients with TTH and migraine.